"Anything you can do, I can do bigger?": the ethics and equity of growth hormone for small normal children. Issue 3 (21st February 2006) - Gill, D G
Abstract : This paper argues against the use of growth hormone (GH) for small normal children ("idiopathic" short stature) with the following considerations: ethical (philosophical) grounds, cost-economic implications, and the rationale for treating normal physiological variation with a potent pharmacological agent. The author would prefer to see health and economic resources being directed to correct nutritional and environmental deprivation among underprivileged groups in preference to providing GH injections for small normal children.